Effect of Apple Pomace Powder Addition on the Physicochemical Properties of Oily Cakes and Ranking Samples by Delphi Fuzzy Approach - Maryam Sabet Ghadam; Mohammad Reza Saeedi Asl; Akram Sharifi; Ahmad Pedram Nia; Mohammad Armin (Journal of Food Quality)
The current study is aimed to compare the effect of fat and/or wheat-flour substitution with apple pomace on the physicochemical and shelf-life of oily cakes. The sensory quality of samples was evaluated using the Delphi-Fuzzy logic method. The oily-cakes include the following: TCO: control; TW10% and TW20%: flour substitution with apple pomace (10 and 20% w/w); TO10% and TO20%: fat substitution with apple pomace (10 and 20% w/w); TW&O5:5 and TW&O10:10: fat and wheat-flour substitution with apple pomace (5 : 5 and 10 : 10% w/w). The lowest and highest protein content were recorded for Tw20% (10.0 ± 0.12%) and TO20% (11.0 ± 0.45%) (p<0.05). There was no significant difference between the fat content of control samples with TW10%, TW20%, and TO&W5:5 (p>0.05). TW20% exhibited the highest fiber content (2.12%) and the lowest caloric (385.0 kcal/100 g) values. There was a significant difference between baking loss of TO10% (9.87%) and TO20% (9.36%) samples with control one (11.6%) (p<0.05). By reducing the fat content, smaller and lower porous was observed. The antioxidant and antimicrobial potential of apple pomace was not significant. Therefore, apple pomace had no significant effect on the shelf-life of cakes. Based on defuzzification values, the sensory ranking of samples was as follows: TCO 64.4>TW20% 63.9>TW&O5:5 63.7>TW10% 63.6>TO10% 60.2>TW&O10:10 60.1>TO20% 58.8. Overall, apple pomace could be considered a cost-effective, sustainable, and healthy alternative to partial wheat-flour. Further research is required to produce reduced-fat cakes. Adding fruit powder along with fat replacers can be suggested for future studies.